Transformasi Karakter Melalui Dakwah: Studi Pembinaan Anak di LPKA Kelas II Bandar Lampung - Rini Setiawati; Khomsahrial Romli (Institut Agama Islam Negeri (IAIN) Curup, 2024)
LPKA is a place where children who are in conflict with the law receive education and counselling. Coaching is the main project carried out by LPKA to improve the quality of devotion to God Almighty, Intellect, Skills, Attitudes, and Behavior, as well as children's welfare. This research was conducted at LPKA Class II Bandar Lampung. Data collection methods used are observation, interviews, documentation, and literature study. The analysis technique used is a qualitative descriptive method, namely each method or approach is described in the form of exposure and data obtained from field data sources. The research results show thatda'wah communication in character building, should be carried out continuously so that the coaching will run well and in accordance with the demands of Islamic teachings, based on religious teachings and using several counseling techniques and using psychological theories to understand the behavior of correctional students in LPKA Klas II Bandar Lampung, but it is still not optimal, this can be seen from the quality of the coaching staff, especially for Islamic religious or spiritual mental development, where there is still a lack of Islamic religious or mental spiritual supervisors with a counseling or psychology background. So that there is still a lack of child observer stakeholders involved in Class II LPKA Bandar Lampung.